Two Birds with One Stone Tailoring Singlet Fission for Both Triplet Yield and Exciton Diffusion Length - Zhu, Tong (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.